-5(2x+8)-4x=8(3-x)-4

Simple and best practice solution for -5(2x+8)-4x=8(3-x)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x+8)-4x=8(3-x)-4 equation:


Simplifying
-5(2x + 8) + -4x = 8(3 + -1x) + -4

Reorder the terms:
-5(8 + 2x) + -4x = 8(3 + -1x) + -4
(8 * -5 + 2x * -5) + -4x = 8(3 + -1x) + -4
(-40 + -10x) + -4x = 8(3 + -1x) + -4

Combine like terms: -10x + -4x = -14x
-40 + -14x = 8(3 + -1x) + -4
-40 + -14x = (3 * 8 + -1x * 8) + -4
-40 + -14x = (24 + -8x) + -4

Reorder the terms:
-40 + -14x = 24 + -4 + -8x

Combine like terms: 24 + -4 = 20
-40 + -14x = 20 + -8x

Solving
-40 + -14x = 20 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-40 + -14x + 8x = 20 + -8x + 8x

Combine like terms: -14x + 8x = -6x
-40 + -6x = 20 + -8x + 8x

Combine like terms: -8x + 8x = 0
-40 + -6x = 20 + 0
-40 + -6x = 20

Add '40' to each side of the equation.
-40 + 40 + -6x = 20 + 40

Combine like terms: -40 + 40 = 0
0 + -6x = 20 + 40
-6x = 20 + 40

Combine like terms: 20 + 40 = 60
-6x = 60

Divide each side by '-6'.
x = -10

Simplifying
x = -10

See similar equations:

| c+3.4=4.3 | | (x-2)(x-7)=20 | | (5x+3)7= | | n+4-6n=-10-6n+5+2n | | 3y-3=2y+6 | | v^2-7v=18 | | 1+4/2=7 | | 4x+9=36 | | 6x^2+9x+6=0 | | -2(8-5a)-a=3a+8 | | 21=(3+2)y | | 5=5t^2-16t+3 | | 18x+17-23x=14-11x-15 | | 2-10k=2k+26 | | 0+3y=11 | | 21=2(y+3) | | -(-85)= | | -4*5=b | | w^2-6w=27 | | 8+3y=11 | | v=1*w*h | | -x-20=-3x+8 | | 8+(3)(0)=11 | | -14-4x=12-2x | | 4+3=n | | x^4=x-6 | | 2(x-9)+1=3(x-3) | | 5+2x=-5 | | -29-x=37+5x | | -[-44]= | | 4e^3x-1.5=360 | | -15+2x=-3x+15 |

Equations solver categories